Model Terapi Seni Dengan Media Visual Untuk Meningkatkan Motivasi Belajar Menghadapi Kurikulum Merdeka Pada Siswa MI Al Ittihad Jakarta Pusat - Safitri M; Sulis Mariyanti; Desy Prastyani; Laiy Roikhatun (Departement of Mathematics Education, 2024)
The Merdeka Curriculum has begun to be implemented at every level of education, so a student approach is needed so that this change can be accepted happily. This shows that students need inner strength that can motivate their desire to learn, one of which is student learning motivation. Motivation can be increased through guidance and counseling at school. It is necessary to provide a pleasant guidance and counseling model that students can accept. The aim of this research is to apply the art therapy model with visual media in guidance and counseling in order to increase student learning motivation. This research method is quantitative with quasi-experiment. The respondents were 72 students in grades 4, 5 and 6 at MI Al Ittihad School, Central Jakarta, where grade 5 was the control. The learning motivation measuring tool is based on Uno theory with 25 valid items and a reliability coefficient of 0.862. The results of the study show that there is a difference in the learning motivation of MI Al Ittihad students before and after art therapy activities with visual media (sig p 0.00), while for the control class there is also a difference but the average score decreased. There were equal numbers of students' motivation before therapy in the high and low categories, after therapy more students' motivation was high. Guidance methods using art therapy through psychodrama, art therapy using visual photo media for groups and individuals which have produced effective results. This suggested method can be applied in guidance and counseling activities that already exist at MI Al Ittihad, where student interaction activities in learning can also be more interactive in welcoming the Independent Curriculum.